Statistical Analysis Approach to Determine Language Quality of Students’ Responses Using WorldNet Similarity Techniques - Ullah, Farhan; Farhan, M.; Malik, K. R.; Iqbal, M. M.; Ibrar, M.; Rahman, Z. (The Nucleus, 2018)
This study aims to electronically assessed (e-assessment) students’ replies in response to teachers’ question. It can be useful to systematize the question answering context regarding matching text semantically through WordNet semantic similarity techniques. WordNet is a lexical database of words’ synonyms. It uses group of synonyms called synsets for semantical operation of English text. For this purpose, a new methodology is proposed to automate e-assessment in the field of education. The collected dataset contains 210 pairs of words extracted from different undergraduate students’ replies in contradiction of teacher’s question statement. Further WordNet similarity measures i.e. Path Length, Lin, Wu &Palmer and Hirst & Onge are used to compute the semantic relatedness score. In the pilot study 42 pair of words were extracted from 8 students’ replies, which are marked using semantic similarity measures and equated with teacher’s marks. Teachers are provided with four boxes of the mark while our developed method provides a precise measure of marks. The experiment is shown with comprehensive dataset resulting with words’ frequencies in similarity measures.